The Influence of Responsiveness, Reliability, and Empathy on Public Service Satisfaction through Perception of Service Quality as an Intervening Variable at Mapilli Community Health Center: JEL Classification: I18, H83, H75, L15, M31 - Whisnu Adiputra; Sucianti Sukiana Sari (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The aim of the current research is to investigate how the responsiveness, reliability, and empathy affect the level of public service satisfaction, in which the perceived service quality is an intermediate variable at the Mapilli Community Health Center. A quantitative style was used and a survey methodology was used to conduct the study by employing the users of community health services. The data were collected through closed-ended questionnaires, non-participatory observation and additional documentation. The methods of analysis included the structure equation modeling that can be varied to evaluate the direct and indirect relationships between the variables. The results showed that responsiveness, reliability, and empathy affected the perceived service quality in a statistically significant positive effect. Responsiveness and empathy also exhibited a statistically significant positive direct impact on the public service satisfaction. Additionally, the perceived service quality showed that it had a strong positive impact on the public service satisfaction. The mediation analysis showed that perceived service quality was a major mediator of the impacts of responsiveness, reliability and empathy on satisfaction with public service. These findings indicate that improving the responsiveness, reliability, and empathy of the health service personnel can strengthen the perceptions of service quality and therefore, improve the satisfaction of the populace. Finally, the paper confirms that perceived service quality is a strategic factor in enhancing the influence of the service quality dimension on the public service satisfaction in the primary health care setting.